Islamic hire purchase law is getting special attention in Malaysia: a socio legal analysis - Md. Abdul , Jalil (Macrothink Institute, USA, 2013)
The Muamalah Hire Purchase Bill (MHPB) was initially prepared by a group of members of the shariah supervisory council of Bank Islam Malaysia Berhad (BIMB) in 1991 and it was later submitted to the Ministry of Domestic Trade and Consumer Affairs in Malaysia and the Central Bank of Malaysia for review. Finally in the year 2000, it was referred to the Attorney General’s Chamber for further examination whether it met the shariah rules and how it could be implemented in Malaysia. However, the Bill could still not be submitted to the Parliament until today for consideration and approval due to certain reasons. The objective of this paper is to discuss the nature of the Islamic hire purchase contract (IHPC) and to compare it with the traditional hire purchase contract (THPC) for purposes to find the difference between the two systems of law. Descriptive and analytical research methodology had been applied in this research paper to analyze the collected data.